Drug Repurposing for Targeting Acute Leukemia With KMT2A (MLL)—Gene Rearrangements - Tsakaneli, Alexia; Williams, Owen (Frontiers in Pharmacology, 2021)
The treatment failure rates of acute leukemia with rearrangements of the Mixed Lineage Leukemia (MLL) gene highlight the need for novel therapeutic approaches. Taking into consideration the limitations of the current therapies and the advantages of novel strategies for drug discovery, drug repurposing offers valuable opportunities to identify treatments and develop therapeutic approaches quickly and effectively for acute leukemia with MLL rearrangements.